Farmers plant Heat Tolerant Maize varieties to improve their food security and livelihood in climate-vulnerable areas of South Asia, on over 20,000 ha - CGIAR Research Program on Maize (2020)
Growing heat-tolerant maize can reduce yield losses due to climate change by up to 36% (rainfed) and 93% (irrigated). Heat Tolerant Maize for Asia (HTMA, 2013-17) helped smallholder farmers in climate-vulnerable ecologies to secure their food security and livelihoods, ensured technologies' equal access to women farmers and incorporated gender-preferred nutrition traits. 50+ CIMMYT maize hybrids have been licensed to public and private partners (2015-2020) for release. By 2020, farmers had adopted 16 varieties on over 20,000 ha.